Co-granulation of bio-ash with sewage sludge and lime for fertilizer use. Issue 4 (December 2016) - Pesonen, Janne; Kuokkanen, Ville; Kuokkanen, Toivo; Illikainen, Mirja
Abstract: Both the current growth strategy and environmental policies of the European Union (EU) aim to increase the amount of renewable energy and to improve the use of waste streams. This will increase the amount of bio-ash from biomass combustion in the future, thereby increasing the need for its utilization, with fertilizer use the most natural target for bio-ash. Wood ash, in particular, contains all the nutrients that plants need, in almost the correct proportions, excluding nitrogen, which is released into the atmosphere during combustion. Nitrogen could be added to ash fertilizers by co-granulating bio-ash, for example, with sewage sludge. However, co-granulation has not been studied extensively. This study investigated co-granulation of bio-ash with sewage sludge and lime. It measured compressive strengths, neutralizing values, and elemental concentrations of the granules. The concentrations of heavy metals (As, Cd, Cr, Cu, Pb, Ni, and Zn) in the granules were sufficiently low not to prevent their use in forest fertilizer use according to Finnish legislation. Overall, the concentrations of nutrients (Ca, K, and P) were reasonably high. The addition of lime improved the neutralizing capacity of the studied granules, and the addition of sewage sludge increased their nitrogen content. The addition of sewage sludge considerably lowered the compressive strength of the granules, and the addition of lime (slaked lime) did not improve the strength of the granules. From a technical point of view, the co-granulation was very successful.